Dehydroxylative Cyanation of Alcohols Promoted by Triphenyphosphine/1,2-Diiodoethane - Luo, Ling; Lin, Jin-Hong; Xiao, Ji-Chang (Synlett, 2023)
A Ph3P/ICH2CH2I-promoted dehydroxylative cyanation of alcohols has been developed. In contrast to previous dehydroxylative cyanation methods that can suffer from several limitations, such as the use of transition metals or moisture-sensitive Lewis acids, this protocol features convenient operations, mild reaction conditions, and the use of cheap and widely available reagents.
Keywords: dehydroxylation; alcohols; cyanation; hydroxyl group; nucleophilic substitution